Ответ:
Пошаговое объяснение:
сначала сокращаем первый множитель:
потом второй:
далее перемножаем:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
сначала сокращаем первый множитель:![\frac{-16}{24} = - \frac{2}{3} \frac{-16}{24} = - \frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-16%7D%7B24%7D%20%3D%20-%20%5Cfrac%7B2%7D%7B3%7D)
потом второй:![\frac{-27}{81} = - \frac{1}{3} \frac{-27}{81} = - \frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-27%7D%7B81%7D%20%3D%20-%20%5Cfrac%7B1%7D%7B3%7D)
далее перемножаем:![- \frac{2}{3} * -\frac{1}{3} - \frac{2}{3} * -\frac{1}{3}](https://tex.z-dn.net/?f=-%20%5Cfrac%7B2%7D%7B3%7D%20%2A%20-%5Cfrac%7B1%7D%7B3%7D)